Honeydew foraging by birds in an Atlantic Forest fragment of Minas Gerais State, Brazil - Teixeira, Fagner Daniel; Azevedo, Fernando Cesar Cascelli de (Biota Neotropica, 2013)
Honeydew foraging by birds has been extensively documented in recent years. However, this interaction has been poorly documented in Brazil, with predominance of few species of birds foraging only in Mimosa scabrella trees. With the objective of describing the behavior of birds interacting with scale insects associated with trees, we conducted a study at the Serra de São José, Tiradentes, in the State of Minas Gerais, Brazil. Observations were recorded from June to July 2012. We observed 13 species of birds feeding on honeydew scale insects, eight never previously recorded. We observed individuals using aerial and surface maneuvers to collect the honeydew on the branches or reaching the droppings below the branches. These species were observed foraging individually, in pairs and also in large groups. Our results suggest that honeydew excretion from scale insects associated with Pseudopiptadenia leptostachya trees represents an important energy source for local birds as observed in fragments of Atlantic Forest in the Minas Gerais State, southeast region of Brazil.